No evidence of predator odor avoidance in a North American bird community - Austin Dotta; Batur Yaman; Alex Van Huynh (Avian Research)
Recent advances in our understanding of avian chemical communication have highlighted the importance of olfaction in many aspects of avian life. Prior studies investigating predator avoidance behaviors in response to predator odor cues have produced mixed results across species and contexts. Here we assess if a community of birds in eastern Pennsylvania displays avoidance behaviors towards predator odor cues in a natural foraging setting. We use clay caterpillars to measure foraging activity by birds in the presence of predator (bobcat) urine, non-predator (rabbit) urine, and water controls in two different environmental contexts (field vs. forest). Although we detected a weak trend for birds to forage less at predator urine-treated sites, we found no significant difference in avian foraging between the site types. We did find that foraging rates between environmental contexts changed significantly over the course of the experiment, with forest sites showing decreasing foraging rates and field sites showing increasing foraging rates. Our results reinforce the published literature that avoidance of predator odors by birds may not be ubiquitous across contexts and species.